Authors (The Biblical archaeology review, 2026)
Ariel Cohen (The Siloam Tunnel Inscription: For the Living or the Dead?) is Associate Professor of Linguistics in the Department of Foreign Literatures and Linguistics at Ben-Gurion University of the Negev, Israel. Thomas Davis (The Diaspora Revolt: Cyprus’s Forgotten Jewish Uprising) was Professor of Archaeology at Lipscomb University and Associate Director of the Lanier Center […]